Corrosion-resistant grinding ball for ball mill as well as preparation method and application of corrosion-resistant grinding ball
The patent addresses the economic and performance limitations of current corrosion-resistant ball mill balls by optimizing the chemical composition and micro/nano carbide distribution, resulting in balls with enhanced corrosion resistance and mechanical properties for use in corrosive environments without relying on expensive metals.
Patent Information
- Application Number
- CN202411809742.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-18
AI Technical Summary
Existing ball mills require high-performance balls that are resistant to corrosion due to exposure to corrosive environments in industries like mining and cement, where current solutions rely on expensive noble metals or complex processes, making them economically inefficient and difficult to control.
A ball mill ball with a specific chemical composition (C 1.9-2.4%, Mn 0.3-0.8%, Cr 10.0-14.0%, Si 0.4-0.8%, Ni+Mo ≤0.05%, V 0.01-0.03%, N 0.002-0.005%, Y 0.01-0.03%, S ≤0.02%, with a Cr:C ratio greater than 5, containing micro and nano carbides, optimized for improved corrosion resistance and mechanical properties without relying on expensive metals.
The optimized ball mill balls exhibit superior corrosion resistance and mechanical properties, extending service life while maintaining economic viability by controlling element ratios and incorporating micro/nano carbides, ensuring effective performance in corrosive environments.
Smart Images

Figure CN119640154A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of grinding ball casting, in particular to a corrosion-resistant grinding ball for a ball mill and a preparation method and application thereof. Background Art
[0002] Grinding balls are a type of wear component with the highest consumption in the field of wear-resistant steel, and are widely used in industries such as mining, cement, and electricity. Among them, cast iron grinding balls are favored due to their relatively simple manufacturing and high hardness. However, with the increasing complexity of the grinding and crushing operating environment, the performance requirements for grinding balls are becoming higher and higher.
[0003] Wet grinding can effectively increase the grinding speed of materials, but it also makes the grinding balls and other materials exposed to the solution environment for a long time. Various chemical substances in the abrasive are immersed in the solution, resulting in an increase in corrosive ions such as chloride ions and sulfate ions in the solution, and the solution is acidic or alkaline, causing corrosion to the grinding balls. This corrosion often accelerates the wear process of the grinding balls, forming abrasion, and seriously reducing the life of the grinding balls. Therefore, improving the corrosion resistance of the grinding balls has become one of the important ways to extend their service life.
[0004] However, the existing corrosion-resistant casting grinding balls mostly use precious metals, such as copper, or add a large amount of chromium, molybdenum, nickel, etc., resulting in general economic efficiency. In addition, the existing corrosion-resistant grinding ball preparation process is complicated and the process is not easy to control.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The object of the present invention is to provide a corrosion-resistant grinding ball for a ball mill and a preparation method and application thereof, aiming to provide a corrosion-resistant grinding ball that does not rely on the addition of multiple precious metal elements.
[0007] The present invention is achieved in that:
[0008] In a first aspect, the present invention provides a corrosion-resistant grinding ball for a ball mill, the chemical composition of which is as follows by mass percentage:
[0009] C 1.9%~2.4%, Mn 0.3%~0.8%, Cr 10.0%~14.0%, Si 0.4%~0.8%, Ni+Mo≤0.05%, V 0.01%~0.03%, N 0.002%~0.005%, Y 0.01%~0.03%, S≤0.02%, P≤0.02%, and the balance is iron and unavoidable impurities.
[0010] In an optional embodiment, the chemical composition is as follows by mass percentage:
[0011] C 2.2%~2.4%, Mn 0.5%~0.8%, Cr 12.0%~14.0%, Si 0.4%~0.8%, Ni0.01%~0.02%, Mo 0.02%~0.03%, V 0.02%~0.03%, N 0.003%~0.005%, Y0.02%~0.03%, S≤0.02%, P≤0.02%, and the balance is iron and unavoidable impurities.
[0012] In an optional embodiment, the mass percentage ratio of Cr to C element is Cr:C>5;
[0013] Preferably, the mass percentage ratio of Cr to C element is 5.26-5.83.
[0014] In an optional embodiment, pearlite, martensite, eutectic carbide and micron and nano carbides are distributed in the matrix of the corrosion-resistant grinding ball for ball mill;
[0015] Preferably, the micron and nanometer carbides dispersed in the matrix include M7C3 and M3C2, with a total volume fraction of 0 to 8%;
[0016] Preferably, the volume fraction of pearlite in the matrix is greater than or equal to 50%.
[0017] In a second aspect, the present invention provides a method for preparing the corrosion-resistant grinding balls for a ball mill according to any one of the aforementioned embodiments, comprising: preparing ingredients according to the chemical composition and content of the corrosion-resistant grinding balls for a ball mill and casting them.
[0018] In an optional embodiment, the method comprises: melting a steel source, a chromium source, a silicon source, a manganese source, a nickel source and a carbon source;
[0019] Before the molten iron is taken out of the furnace, it is treated with vanadium-nitrogen alloy to optimize the structure in the furnace. Then the molten iron is poured into a ladle containing Y source additives to complete the optimization of the structure in the ladle.
[0020] After the temperature of the molten iron drops to the pouring temperature, pouring and molding are carried out.
[0021] In an optional embodiment, the raw material is melted in a medium frequency induction melting furnace, and the melting temperature is controlled to be 1600° C. to 1700° C.;
[0022] Preferably, the furnace structure optimization treatment starts 7 to 10 minutes before the molten iron is discharged from the furnace and is carried out under stirring conditions.
[0023] In an optional embodiment, a Y source additive coated with iron sheet is added to the ladle in advance, and after the molten iron is poured in, the ladle is subjected to an internal structure optimization treatment, and then the ladle is allowed to stand for slag removal before pouring;
[0024] Preferably, the Y source additive coated with iron sheet is yttrium iron;
[0025] Preferably, the total mass of each package of the iron sheet-coated Y source additive is 100g-500g, and the weight of the Y source in each package is not higher than 100g;
[0026] Preferably, the pouring temperature is 1400°C to 1450°C.
[0027] In an optional embodiment, the method further comprises: performing a quenching heat treatment after the casting;
[0028] Preferably, the quenching heat treatment is a single-pass quenching heat treatment;
[0029] Preferably, the quenching heat treatment comprises: heating the grinding ball casting to 1020°C to 1060°C at a rate of 50°C / h to 80°C / h, then keeping the temperature for 5h to 7h, and then oil cooling to room temperature.
[0030] In a third aspect, the present invention provides the use of the corrosion-resistant grinding balls for ball mills according to any of the aforementioned embodiments or the corrosion-resistant grinding balls for ball mills prepared by any of the preparation methods according to the aforementioned embodiments in processing materials containing corrosive media in a ball mill or a semi-autogenous mill;
[0031] Preferably, the corrosive medium material contains chloride ions.
[0032] The present invention has the following beneficial effects: the grinding balls provided by the present invention contain elements such as C, Mn, Cr, Si, V, N, and Y. By adjusting the chemical composition and content of the grinding balls, grinding balls with excellent corrosion resistance and good mechanical properties are obtained. The contents of C and Cr are coordinated with each other, so that the grinding balls have sufficient Cr in a solid solution state under the premise of ensuring sufficient eutectic carbide formation, avoiding excessive consumption of Cr by C and too low amount of Cr remaining in the matrix, resulting in poor corrosion resistance; in addition, the economic efficiency of the grinding balls will not be reduced due to the addition of too much Cr and other precious metal elements. The synergistic addition of V and N in the grinding balls provided by the present invention has the optimization effects of carbide toughening and microstructure refinement, and the VN compound formed first promotes the refinement of the matrix microstructure and carbides, and V solid solution enhances the matrix hardness and carbide toughening. In addition, Y in the grinding balls can further remove impurities inside the organization, improve the composition of inclusions in the grinding balls and the potential difference with the matrix, and optimize the grinding ball organization in the form of fine oxides, thereby improving the corrosion resistance of the grinding balls while ensuring their mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0034] Figure 1 A panoramic scanning electron microscope photograph of the corrosion-resistant wear ball provided in Example 1 of the present invention;
[0035] Figure 2 This is a scanning electron microscope photograph of the corrosion-resistant grinding ball matrix structure provided in Example 1 of the present invention. DETAILED DESCRIPTION
[0036] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0037] The embodiment of the present invention provides a corrosion-resistant grinding ball for a ball mill, and the chemical composition thereof, measured by mass percentage, is as follows: C 1.9%-2.4%, Mn 0.3%-0.8%, Cr 10.0%-14.0%, Si 0.4%-0.8%, Ni+Mo≤0.05%, V 0.01%-0.03%, N 0.002%-0.005%, Y 0.01%-0.03%, S≤0.02%, P≤0.02%, and the remainder is iron and unavoidable impurities.
[0038] It should be noted that the corrosion-resistant grinding balls for ball mills provided in the embodiments of the present invention contain elements such as C, Mn, Cr, Si, V, N, and Y. The contents of C and Cr are coordinated with each other. The synergistic addition of V and N can achieve the optimization effects of carbide toughening and microstructure refinement. Y can further remove impurities inside the microstructure. By optimizing the overall chemical composition, the corrosion resistance of the grinding balls can be improved while ensuring their mechanical properties.
[0039] In a preferred embodiment, the chemical composition is as follows by mass percentage: C 2.2% to 2.4%, Mn 0.5% to 0.8%, Cr 12.0% to 14.0%, Si 0.4% to 0.8%, Ni 0.01% to 0.02%, Mo 0.02% to 0.03%, V 0.02% to 0.03%, N 0.003% to 0.005%, Y 0.02% to 0.03%, S ≤ 0.02%, P ≤ 0.02%, and the balance is iron and unavoidable impurities. By further optimizing the dosage of each element, the corrosion resistance and mechanical properties can be improved at the same time.
[0040] In a preferred embodiment, the mass percentage ratio of Cr to C is Cr:C>5; more preferably, the mass percentage ratio of Cr to C is 5.26-5.83. It is appropriate to control the mass percentage of Cr and C within the above range, so that the grinding ball has a sufficient amount of Cr in solid solution state under the premise of ensuring sufficient eutectic carbide formation, avoiding excessive consumption of Cr by C and too low amount remaining in the matrix, which makes it difficult to ensure corrosion resistance; in addition, the economic efficiency of the grinding ball will not be reduced due to the addition of too much Cr and other precious metal elements.
[0041] Specifically, in the corrosion-resistant grinding balls for ball mills provided in the embodiments of the present invention, the effects of various elements on the performance thereof are as follows:
[0042] C element: It is one of the most important elements in wear-resistant cast iron. It is a constituent element of the wear-resistant hard phase in cast iron, namely carbide. Its content greatly affects the hardness, toughness and corrosion resistance of the grinding ball. The grinding ball of the embodiment of the present invention is a grinding ball for use in a corrosive environment. If the C content is too high, more matrix-carbide interfaces will be introduced, aggravating galvanic corrosion and crevice corrosion. Therefore, it cannot be too high. The embodiment of the present invention controls the C content within 1.9% to 2.4%, which can take into account both the hardness and wear resistance of the grinding ball.
[0043] Cr element: It is one of the most important elements in wear-resistant cast iron. It is a component element of the wear-resistant hard phase, namely carbide, in cast iron. Its content greatly affects the hardness, toughness and corrosion resistance of the grinding ball, but it is also one of the most important elements affecting the cost and economy of the grinding ball. Increasing the Cr content helps to generate more hard carbides, and can also be dissolved in the matrix to improve corrosion resistance. In the embodiment of the present invention, the Cr content is controlled at 10.0% to 14.0%, and it needs to match the C element content (Cr: C>5), which can make the grinding ball have better corrosion resistance, but the cost of the grinding ball will not be high. If the Cr content is too high, it will lead to a significant increase in cost and no significant improvement in corrosion resistance; if the Cr content is too low, it will lead to a significant decrease in corrosion resistance.
[0044] Mn element: It is an element that promotes austenitization. Adding it to the grinding balls can play a certain role in deoxidation and desulfurization, and can also improve the work hardening ability of the grinding balls under impact to a certain extent. However, adding too much Mn element will affect the toughness and corrosion resistance of the grinding balls. The embodiment of the present invention controls the Mn content to 0.3% to 0.8%, which can take into account the deoxidation, work hardening, toughness and corrosion resistance of the grinding balls. If the Mn content is too high, it will affect the toughness and corrosion resistance of the grinding balls; if the Mn content is too low, it will lead to a decrease in work hardening performance and will also affect the deoxidation and desulfurization effects.
[0045] Si element: It is one of the deoxidizing elements in the grinding ball, which can promote solid solution to achieve strengthening, and can improve the corrosion resistance of the grinding ball to a certain extent, but too high a content will reduce the toughness of the grinding ball. The embodiment of the present invention controls the Si content to 0.4% to 0.8%, which can improve the corrosion resistance while ensuring the toughness of the grinding ball. If the Si content is too high, the mechanical properties such as the toughness of the grinding ball will be significantly reduced; if the Si content is too low, the corrosion resistance of the grinding ball will be reduced.
[0046] Ni element: It is a beneficial element for improving the corrosion resistance of cast iron, and can also improve the toughness of cast iron to a certain extent, but it will increase the cost of grinding balls and affect their economic efficiency. In the embodiment of the present invention, the addition of Ni is controlled within 0.05% in combination with Mo, which can improve the corrosion resistance and mechanical properties of grinding balls while ensuring low costs. If the Ni content is too high, the cost will increase significantly, but the corrosion resistance and mechanical properties will not increase significantly.
[0047] Mo element: It is a beneficial element for improving the corrosion resistance of cast iron, and can improve the hardenability and hardenability of grinding balls, but it will increase the cost of grinding balls and affect their economic efficiency. In the embodiment of the present invention, the addition of Ni and Mo is controlled within 0.05%, which can effectively improve the corrosion resistance and mechanical properties of the grinding balls without significantly increasing the cost. Similar to Ni, if the Mo content is too high, it will lead to a significant increase in cost, but the corrosion resistance and mechanical properties will not be significantly increased.
[0048] V and N elements: V in the grinding balls will not only be dissolved in the matrix, but also participate in the formation of carbides, but too high a content will lead to the formation of coarse carbides, affecting the toughness of the grinding balls. N is a strong solid-solution element of the grinding balls, which helps to improve the corrosion resistance of the grinding balls, but it is easy to cause the grinding balls to become brittle when added alone. The present invention selects to add V and N elements in conjunction, controls the V content within 0.01% to 0.03%, and controls the N content within 0.002% to 0.005%, preferentially promotes the formation of VN compounds in the grinding balls, and then optimizes the grinding ball structure to avoid brittleness.
[0049] Y element: It has a strong deoxidizing ability in the grinding ball, and can improve the size of the grinding ball structure, including the matrix and carbide, by forming fine oxides, remove the deterioration effect, and improve the inclusion composition to reduce its corrosion sensitivity. The embodiment of the present invention controls the Y content to 0.01-0.03%, which can enhance the deoxidizing ability while avoiding the subsequent increase in slag removal process. If the Y content is too high, it will increase the difficulty of impurity removal during the smelting process and increase the slag removal process; if the Y content is too low, it will affect the size of the grinding ball structure and the corrosion sensitivity of the grinding ball.
[0050] As impurity elements, P and S seriously damage the plasticity and toughness of steel and reduce corrosion resistance. The content of P and S is controlled at ≤0.02%.
[0051] Furthermore, pearlite, martensite, eutectic carbide and micron and nano carbides are distributed in the matrix of the corrosion-resistant grinding ball for ball mill, and there are multiple microstructures. Among them, micron and nano carbides are dispersed in the matrix, including M7C3 and M3C2, and the overall volume fraction is ≤8%, such as 8%, 7%, 6%, 5%, 4%, 3%, 2%, 1%, etc.; the volume fraction of pearlite in the matrix is greater than or equal to 50%, such as 50%, 60%, 70%, 80%, 90%, etc.
[0052] Specifically, pearlite is in lamellar form, which can ensure the toughness and corrosion resistance of the grinding ball. Martensite is in lath or needle form, which can ensure the hardness and wear resistance of the matrix. Eutectic carbide is distributed in a network, which is the main source of wear resistance of the grinding ball. Micron and nano carbide particles are small, and can play a role in strengthening and toughening when the amount is appropriate, but too much precipitation will reduce the impact work of the grinding ball and cause corrosion.
[0053] The embodiment of the present invention provides a method for preparing a corrosion-resistant grinding ball for a ball mill, wherein the chemical composition and content of the corrosion-resistant grinding ball for a ball mill provided by the embodiment of the present invention are used to prepare the materials and cast the materials. By adjusting the chemical composition and content of the grinding ball, a grinding ball with excellent corrosion resistance and good mechanical properties is obtained.
[0054] The specific steps of the preparation method provided in the embodiment of the present invention are described below:
[0055] S1. Melting
[0056] According to the chemical composition and content of the corrosion-resistant grinding balls, the raw materials are added into a smelting furnace, and steel source, chromium source, silicon source, manganese source, nickel source and carbon source are first added, and the temperature is raised to melt.
[0057] In some embodiments, the raw material can be melted in a medium frequency induction melting furnace, and the melting temperature can be controlled to be 1600° C. to 1700° C. to fully melt the raw material. Specifically, the melting temperature can be controlled to be 1600° C., 1630° C., 1650° C., 1680° C., 1700° C., etc.
[0058] S2. Furnace structure optimization treatment
[0059] Before the molten iron is discharged from the furnace, vanadium-nitrogen alloy is added according to the percentage of components to optimize the structure in the furnace, preferentially promoting the formation of VN compounds in the grinding balls, thereby optimizing the grinding ball structure.
[0060] In some embodiments, the in-furnace structure optimization treatment starts 7 to 10 minutes before the molten iron is discharged from the furnace, and the structure optimization treatment should be fully stirred. Specifically, the timing of adding the vanadium-nitrogen alloy is precisely controlled to be 7 to 10 minutes (such as 7 minutes, 8 minutes, 9 minutes, 10 minutes, etc.) before the molten iron is discharged from the furnace, which has a better structure optimization effect. If the vanadium-nitrogen alloy is added too early, it is easy to cause the vanadium-nitrogen precipitates to be removed as impurities.
[0061] S3, optimization of the internal structure and pouring
[0062] After the in-furnace structure optimization treatment, the molten iron is poured into a ladle containing a Y source additive, and the ladle structure optimization treatment is completed in the ladle; after the molten iron temperature drops to the pouring temperature, the molten iron is poured to obtain the grinding ball casting. The pouring temperature can be 1400°C to 1450°C, such as 1400°C, 1410°C, 1420°C, 1430°C, 1440°C, 1450°C, etc.
[0063] In some embodiments, a Y source additive coated with iron sheet is sprinkled into the ladle in advance, and after the molten iron is poured in, the ladle structure optimization treatment is performed, and then the ladle can be left to stand for one time to remove slag before pouring. The use of the Y source additive coated with iron sheet can better play the role of Y element in forming fine oxides to improve the size of the grinding ball structure. If the iron sheet is not coated, the Y element is likely to be burned and oxidized before it has time to diffuse and play a role.
[0064] Further, the iron sheet coated Y source additive is yttrium iron, and the total mass of each package of the iron sheet coated Y source additive is 100g-500g (such as 100g, 200g, 300g, 400g, 500g, etc.), and the weight of the Y source in each package is not more than 100g, so as to better protect the Y source additive. Specifically, the iron sheet coated Y source additive can be a commercially available material.
[0065] Specifically, the static slag removal can adopt conventional slag removal means, such as adding a slag removal agent to remove the slag.
[0066] S4, quenching heat treatment
[0067] After casting, quenching heat treatment is performed. The preparation method provided in the embodiment of the present invention only needs to undergo a single quenching heat treatment after casting, and does not require a complicated quenching heat treatment process.
[0068] In some embodiments, the quenching heat treatment includes: heating the grinding ball casting to 1020°C to 1060°C at a rate of 50°C / h to 80°C / h, then keeping the temperature for 5h to 7h, and then cooling to room temperature by oil cooling. The quenching heat treatment can improve the rigidity, hardness and wear resistance of the grinding ball.
[0069] Specifically, the heating rate of the grinding ball casting can be 50℃ / h, 60℃ / h, 70℃ / h, 80℃ / h, etc., the quenching temperature after heating can be 1020℃, 1030℃, 1040℃, 1050℃, 1060℃, etc., and the holding time can be 5.0h, 5.5h, 6.0h, 6.5h, 7.0h, etc.
[0070] It should be noted that the method for preparing the corrosion-resistant grinding balls for the ball mill provided in the embodiment of the present invention has the following advantages:
[0071] (1) The smelting process can be obtained by the most common medium frequency furnace smelting method, which can be carried out in an atmospheric environment, eliminating the complex processes such as atmosphere protection, converter refining, forging, and multi-pass rolling, thus saving process costs.
[0072] (2) During the smelting process, through two structural optimization treatments in the furnace and the ladle, the melt is refined, the structure is refined, and the corrosion sensitivity is reduced. At the same time, a harder and tougher grinding ball is obtained by carbide toughening and matrix strengthening.
[0073] (3) The subsequent heat treatment is simple and the process is short. It relies on high temperature solid solution insulation to fully dissolve the carbides on the matrix, reduce the risk of galvanic corrosion in a corrosive environment, and improve the stability of the matrix in subsequent quenching. In the subsequent transformation, the matrix does not fully form martensite, but is replaced by a high proportion of pearlite, thereby ensuring the toughness and corrosion resistance of the grinding ball while taking into account its hardness.
[0074] The corrosion-resistant grinding balls for ball mills provided in the embodiments of the present invention have excellent corrosion resistance and can be used in ball mills or semi-autogenous mills to process materials containing corrosive media. They are specifically suitable for applications in scenarios such as mines, power plants, and cement plants.
[0075] The type of corrosive medium material is not limited, such as chloride ion-containing. The corrosion-resistant grinding ball for ball mill provided by the embodiment of the present invention has a hardness of ≥57HRC, an unnotched room temperature impact absorption energy of ≥4.5J, and a linear polarization resistance of ≥2200Ω in a corrosive environment containing 2% chloride ions, and has very good corrosion resistance.
[0076] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0077] Example 1
[0078] The present embodiment provides a corrosion-resistant grinding ball for a ball mill, whose chemical composition, measured by mass percentage, includes: C: 2.2%, Mn: 0.8%, Cr: 12.0%, Si: 0.4%, Ni: 0.02%, Mo: 0.02%, V: 0.03%, N: 0.005%, Y: 0.02%, S≤0.02%, P≤0.02%, and the remainder is iron and unavoidable impurities, wherein the mass percentage ratio Cr:C=5.45.
[0079] This embodiment also provides a method for preparing corrosion-resistant grinding balls for a ball mill, and the method comprises the following steps:
[0080] (1) Add steel source, chromium source, silicon source, manganese source, nickel source and carbon source in proportion to the medium frequency furnace and mix them for smelting. During smelting, the temperature of the molten steel rises to 1620°C to fully melt.
[0081] (2) Add vanadium-nitrogen alloy 8 minutes before steel is tapped from the medium frequency furnace to optimize the in-furnace structure, and stir thoroughly during the treatment.
[0082] (3) Pre-sprinkle the Y source additive (specifically yttrium iron) wrapped in iron sheet into the ladle, pour the molten iron obtained in step (2) into it and perform the structure optimization treatment, and after the treatment, let it stand for one time to remove the slag. After the molten iron is cooled to 1420°C, pour the molten iron to obtain the grinding ball casting.
[0083] (4) The grinding ball casting obtained in step (3) was heated to 1040°C at a rate of 60°C / h, kept at this temperature for 6 hours, and then oil-cooled to room temperature.
[0084] The grinding ball sample provided in this embodiment was placed under a scanning electron microscope for observation, and the following results were obtained: Figure 1 The panoramic result shown is Figure 1 It can be seen that the corrosion-resistant grinding ball provided in this embodiment contains eutectic carbide, matrix structure, and different types of carbide particles existing on the matrix structure. Further observation of the matrix structure in high magnification mode yields the following: Figure 2 The photos shown are by Figure 2 It can be seen that the matrix contains a high proportion of pearlite structure, a small amount of martensite, and a certain amount of micron and nano carbides including M7C3 and M3C2, etc. The proportions of each part are as follows: pearlite: 83%, martensite: 10%, carbide: 7%.
[0085] Example 2
[0086] The present embodiment provides a corrosion-resistant grinding ball for a ball mill, whose chemical composition, measured by mass percentage, includes: C: 2.4%, Mn: 0.5%, Cr: 14.0%, Si: 0.8%, Ni: 0.01%, Mo: 0.03%, V: 0.02%, N: 0.003%, Y: 0.03%, S≤0.02%, P≤0.02%, and the remainder is iron and unavoidable impurities, wherein the mass percentage ratio Cr:C=5.83.
[0087] This embodiment also provides a method for preparing corrosion-resistant grinding balls for a ball mill, and the method comprises the following steps:
[0088] (1) Add steel source, chromium source, silicon source, manganese source, nickel source and carbon source in proportion to the medium frequency furnace and mix them for smelting. During smelting, the temperature of the molten steel rises to 1650°C to fully melt.
[0089] (2) Add vanadium-nitrogen alloy 10 minutes before steel is tapped from the medium frequency furnace to optimize the in-furnace structure, and stir thoroughly during the treatment.
[0090] (3) Pre-sprinkle the Y source additive wrapped in iron sheet in the ladle (same as in Example 1), pour the molten iron obtained in step (2) into it and perform the structure optimization treatment, after which the molten iron should be left to stand for slag removal. After the molten iron is cooled to 1400°C, the molten iron is poured to obtain the grinding ball casting.
[0091] (4) The grinding ball casting obtained in step (3) is heated to 1060° C. at a rate of 50° C. / h, kept at this temperature for 7 h, and then oil-cooled to room temperature to obtain a corrosion-resistant grinding ball.
[0092] Example 3
[0093] The present embodiment provides a corrosion-resistant grinding ball for a ball mill, whose chemical composition, measured by mass percentage, includes: C: 1.9%, Mn: 0.4%, Cr: 10.0%, Si: 0.6%, Ni: 0.03%, Mo: 0.02%, V: 0.01%, N: 0.002%, Y: 0.01%, S≤0.02%, P≤0.02%, and the remainder is iron and unavoidable impurities, wherein the mass percentage ratio Cr:C=5.26.
[0094] This embodiment also provides a method for preparing corrosion-resistant grinding balls for a ball mill, and the method comprises the following steps:
[0095] (1) Add steel source, chromium source, silicon source, manganese source, nickel source and carbon source in proportion to the medium frequency furnace and mix them for smelting. During smelting, the temperature of the molten steel rises to 1600°C and is fully melted.
[0096] (2) Add vanadium-nitrogen alloy 7 minutes before steel is tapped from the medium frequency furnace to optimize the in-furnace structure, and stir thoroughly during the treatment.
[0097] (3) Pre-sprinkle the Y source additive wrapped in iron sheet in the ladle (same as in Example 1), pour the molten iron obtained in step (2) into it and perform the structure optimization treatment, after which the molten iron should be left to stand for slag removal. After the molten iron is cooled to 1450°C, the molten iron is poured to obtain the grinding ball casting.
[0098] (4) The grinding ball casting obtained in step (3) is heated to 1020° C. at a rate of 80° C. / h, kept at this temperature for 5 h, and then oil-cooled to room temperature to obtain a corrosion-resistant grinding ball.
[0099] Comparative Example 1
[0100] This comparative example provides a grinding ball for a ball mill, whose chemical composition, measured by mass percentage, includes: C: 2.2%, Mn: 0.8%, Cr: 12.0%, Si: 0.4%, Ni: 0.02%, Mo: 0.02%, S≤0.02%, P≤0.02%. The preparation method of the grinding ball is similar to that of Example 1, except that the structure optimization treatment in steps (2) and (3) is not performed.
[0101] Comparative Example 2
[0102] This comparative example provides a grinding ball for a ball mill, whose chemical composition, measured by mass percentage, includes: C: 2.4%, Mn: 0.8%, Cr: 10.0%, Si: 0.4%, Ni: 0.02%, Mo: 0.02%, V: 0.03%, N: 0.005%, Y: 0.02%, S≤0.02%, P≤0.02%, and the rest are iron and unavoidable impurities, wherein the mass percentage ratio Cr:C=4.16, and the preparation method of the grinding ball is the same as that in Example 1.
[0103] Comparative Example 3
[0104] This comparative example provides a grinding ball for a ball mill, whose chemical composition, measured by mass percentage, includes: C: 2.2%, Mn: 0.8%, Cr: 12.0%, Si: 0.4%, Ni: 0.02%, Mo: 0.02%, V: 0.03%, Y: 0.02%, S≤0.02%, P≤0.02%. The preparation method of the grinding ball is similar to that of Example 1, except that the structure optimization in step (2) only uses ferrovanadium treatment instead of the vanadium-nitrogen alloy treatment in Example 1.
[0105] Comparative Example 4
[0106] This comparative example provides a grinding ball for a ball mill, and its chemical composition includes, by mass percentage: C: 2.2%, Mn: 0.8%, Cr: 12.0%, Si: 0.4%, Ni: 0.02%, Mo: 0.02%, V: 0.03%, N: 0.005%, Re: 0.02%, S≤0.02%, P≤0.02%, and the balance is iron and inevitable impurities. The preparation method of the grinding ball is roughly the same as that of Example 1, that is, compared with Example 1, the comparative example uses mixed rare earth Re as a material for optimizing the internal structure of the package. Mixed rare earth refers to mixed rare earth such as rare earth copper alloy lanthanum cerium, with a molecular formula of CeLaNdPr and a molecular weight of 564.17.
[0107] Comparative Example 5
[0108] This comparative example provides a grinding ball for a ball mill, the chemical composition of which is the same as that of Example 1. The preparation method of the grinding ball is similar to that of Example 1, except that the insulation temperature in step (4) is 960°C.
[0109] Comparative Example 6
[0110] This comparative example provides a grinding ball for a ball mill, the chemical composition of which is the same as that of Example 1, except that in the heat treatment step, the quenching step is as follows: the grinding ball casting is heated to 1040°C at a rate of 60°C / h, then kept at that temperature for 6 hours, and then cooled to room temperature using a cooling solvent, the cooling solvent being air or water. The grinding ball for a ball mill provided in this comparative example cracked directly after water-cooling quenching and could not be used, and the subsequent performance data is the data of the grinding ball obtained by cooling in air.
[0111] Comparative Example 7
[0112] The only difference from Example 1 is that no Y element is added, that is, no Y source additive wrapped in iron sheet is added to the ladle in step (3).
[0113] Comparative Example 8
[0114] The only difference from Example 1 is that the content of Mn is 1.0%.
[0115] Test Example 1
[0116] The ball mills provided in Examples 1 to 3 and Comparative Examples 1 to 6 were subjected to performance testing. The test results are shown in Table 1. The test method is as follows:
[0117] (1) The hardness test is carried out in accordance with GB / T230.1 Metal Rockwell Hardness Test;
[0118] (2) Impact toughness is measured according to the Charpy pendulum impact test method for metallic materials in accordance with GB / T 229, and the specimen is an unnotched specimen;
[0119] (3) The corrosion test is carried out in a 2% NaCl solution in accordance with the applicable practice of electrochemical measurement methods for corrosion tests of metals and alloys in GB / T 40299, and the linear polarization resistance value is used to measure the corrosion resistance (the greater the resistance, the higher the corrosion resistance);
[0120] (4) The wear resistance test was evaluated using the China Foundry Association Standard T-CFA010604.05 2017 Iron and Steel Material Impact Corrosion Abrasive Wear Test Method. The wear resistance of Comparative Example 1 was 1, and the relative wear resistance of the remaining materials was listed. Among them, relative wear resistance > 1 indicates that the wear resistance is better than that of Comparative Example 1.
[0121] Table 1 Properties of wear-resistant alloy cast steel
[0122]
[0123] It can be seen from Table 1 that the hardness, impact absorption energy, and corrosion resistance, i.e., wear resistance, of Examples 1 to 3 are better than those of the comparative example as a whole.
[0124] Comparative Example 1 is a white cast iron material Cr12 of a similar system with a carbon content and a Cr content equivalent to those of the present application, which is a wear-resistant cast iron currently commonly used for grinding balls. The present invention optimizes the ratio and preparation method to make the corrosion resistance and wear resistance of the corrosion-resistant grinding balls provided by the embodiments of the present invention improved by 18.7% and 18% respectively compared with those of Comparative Example 1. At the same time, the corrosion-resistant grinding balls of the embodiments of the present invention have higher room temperature impact absorption energy and better service safety.
[0125] In Comparative Example 2, the mass percentage ratio Cr:C is too small, resulting in a significant decrease in linear polarization resistance and wear resistance.
[0126] Comparative Example 3 uses vanadium iron treatment to replace the vanadium nitrogen alloy treatment, resulting in a significant decrease in linear polarization resistance and wear resistance.
[0127] In Comparative Example 4, rare earth Y is replaced by mixed rare earth, resulting in a significant decrease in impact absorption energy, linear polarization resistance, and wear resistance.
[0128] Comparison of quenching temperature and cooling method between Comparative Example 5 and Comparative Example 6 shows that exceeding the range defined by the present invention will lead to a significant decrease in hardness, impact absorption energy, linear polarization resistance, and wear resistance.
[0129] Comparative Example 7 did not use the tissue optimization treatment of the rare earth Y in the package, resulting in a decrease in the overall performance.
[0130] In Comparative Example 8, more Mn element was added, resulting in a decrease in impact absorption energy, linear polarization resistance and wear resistance.
[0131] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A corrosion-resistant grinding ball for a ball mill, characterized in that: Its chemical composition by mass percentage is as follows: C 1.9%~2.4%, Mn 0.3%~0.8%, Cr 10.0%~14.0%, Si 0.4%~0.8%, Ni+Mo≤0.05%, V 0.01%~0.03%, N 0.002%~0.005%, Y 0.01%~0.03%, S≤0.02%, P≤0.02%, and the balance is iron and unavoidable impurities.
2. The corrosion-resistant grinding ball for ball mill according to claim 1, characterized in that: Its chemical composition by mass percentage is as follows: C 2.2%~2.4%, Mn 0.5%~0.8%, Cr 12.0%~14.0%, Si 0.4%~0.8%, Ni0.01%~0.02%, Mo 0.02%~0.03%, V 0.02%~0.03%, N 0.003%~0.005%, Y0.02%~0.03%, S≤0.02%, P≤0.02%, and the balance is iron and unavoidable impurities.
3. The corrosion-resistant grinding ball for ball mill according to claim 1 or 2, characterized in that: The mass percentage ratio of Cr and C elements is Cr:C>5; Preferably, the mass percentage ratio of Cr to C element is 5.26-5.
83.
4. The corrosion-resistant grinding ball for ball mill according to claim 1, characterized in that: Pearlite, martensite, eutectic carbide and micron and nanometer carbides are distributed in the matrix of the corrosion-resistant grinding ball for ball mill; Preferably, the micron and nanometer carbides dispersed in the matrix include M7C3 and M3C2, with a total volume fraction of 0 to 8%; Preferably, the volume fraction of the pearlite in the matrix is greater than or equal to 50%.
5. A method for preparing the corrosion-resistant grinding balls for a ball mill according to any one of claims 1 to 4, characterized in that: include: The corrosion-resistant grinding balls for the ball mill are prepared according to their chemical composition and content and cast into shape.
6. The preparation method according to claim 5, characterized in that: include: Melting a steel source, a chromium source, a silicon source, a manganese source, a nickel source and a carbon source; Before the molten iron is taken out of the furnace, it is treated with vanadium-nitrogen alloy to optimize the structure in the furnace. Then the molten iron is poured into a ladle containing Y source additives to complete the optimization of the structure in the ladle. After the temperature of the molten iron drops to the pouring temperature, pouring and molding are carried out.
7. The preparation method according to claim 6, characterized in that: The raw materials are melted in a medium frequency induction melting furnace, and the melting temperature is controlled to be 1600°C to 1700°C; Preferably, the furnace structure optimization treatment starts 7 to 10 minutes before the molten iron is discharged from the furnace and is carried out under stirring conditions.
8. The preparation method according to claim 6, characterized in that: Add iron-coated Y source additives into the ladle in advance, optimize the structure of the ladle after the molten iron is poured in, then let it stand to remove slag before pouring; Preferably, the Y source additive coated with iron sheet is yttrium iron; Preferably, the total mass of each package of the iron sheet-coated Y source additive is 100g-500g, and the weight of the Y source in each package is not higher than 100g; Preferably, the pouring temperature is 1400°C to 1450°C.
9. The preparation method according to claim 6, characterized in that: Also includes: After casting, quenching heat treatment is carried out; Preferably, the quenching heat treatment is a single-pass quenching heat treatment; Preferably, the quenching heat treatment comprises: heating the grinding ball casting to 1020°C to 1060°C at a rate of 50°C / h to 80°C / h, then keeping the temperature for 5h to 7h, and then oil cooling to room temperature.
10. Use of the corrosion-resistant grinding balls for ball mills as claimed in any one of claims 1 to 4 or the corrosion-resistant grinding balls for ball mills prepared by the preparation method as claimed in any one of claims 5 to 9 in processing materials containing corrosive media in a ball mill or a semi-autogenous mill; Preferably, the corrosive medium material contains chloride ions.